COVID-19 undermines incomes, livelihoods in rural Myanmar - Ragasa, Catherine; Lambrecht, Isabel B.; Mahrt, Kristi; Aung, Zin Wai; Wang, Michael (International Food Policy Research Institute, 2022)
As the COVID-19 pandemic unfolded in early 2020, Myanmar avoided an early wave of infections. However, even before its first cases were confirmed, the country faced a related economic crisis. Border closures, movement restrictions, and reduced international demand for Myanmar’s goods and services severely affected the nation’s forecasted economic growth. In late 2020, Myanmar also experienced two waves of COVID-19 infections and lockdown measures, followed by a political crisis beginning in February 2021. This combination of widespread COVID-19 and political turmoil has had substantial negative impacts on the nation’s population.